Interactivity in online chat: Conversational cues and visual cues in the service recovery process - Huang, Yingying; Gursoy, Dogan; Zhang, Meng; Nunkoo, Robin; Shi, Si (International journal of information management, 2021)
•The paper investigates interactivity in online chat.•Verbal cues lead to higher perception of an agent’s competence.•Visual nonverbal cues result in higher warmth perceptions.•Visual nonverbal cues have a compensatory effect on message interactivity.•Perceived warmth and competence mediate the effects of verbal and nonverbal cues. Use of both verbal and nonverbal cues in computer-mediated communication can influence customers’ perceptions and their behavioral intentions. Drawing on the compensation effect theory, this study investigates how verbal and nonverbal cues used by customer service agents during online service recovery processes affect customers’ perceptions of service chat agents’ warmth and competence and their willingness to cooperate with a service agent to complete the service recovery process. A 2 (message interactivity cues: high vs. low) × 2 (visual cues: high vs. low) between-subjects experimental design is utilized to identify the main and interaction effects of verbal and visual nonverbal cues used in online communications on customers attitudes and behaviors. Results show that use of verbal cues leads to higher perception of a chat agent’s competence, but lower perception of a chat agent’s warmth while use of visual nonverbal cues results in higher warmth perceptions but lower competence perceptions. The interaction effect of verbal and visual nonverbal cues indicates that visual nonverbal cues have a compensatory effect on message interactivity and vice versa, such that customer-perceived warmth and competence are prone to trade-offs between verbal cues and visual nonverbal cues. Furthermore, perceived warmth and competence mediate the indirect effects of verbal and nonverbal cues on customers’ cooperation intentions. Theoretical and practical implications of use of verbal and nonverbal cues during online communications in service recovery processes are discussed.